2245G/A polymorphism of the receptor for advanced glycation end-products (RAGE) gene is associated with diabetic retinopathy in the Malaysian population - Ng, Zhi Xiang; Kuppusamy, Umah Rani; Tajunisah, Iqbal; Fong, Kenneth Choong Sian; Koay, Adrian Choon Aun; Chua, Kek Heng (BMJ Publishing Group, 2012)
Background/aims The receptor for advanced glycation end-products (RAGE) has been implicated in the pathogenesis of diabetic microvascular complications. The aim of this study was to investigate the association between 2245G/A gene polymorphism of the RAGE gene and retinopathy in Malaysian type 2 diabetic patients. Methods 342 unrelated type 2 diabetic patients (171 with retinopathy (DR), 171 without retinopathy (DNR)) and 235 unrelated healthy subjects from all over Malaysia were recruited for this study. Genomic DNA was isolated from 3âml samples of whole blood using a modified conventional DNA extraction method. The genotype and allele frequencies of 2245G/A were studied using the polymerase chain reactionârestriction fragment length polymorphism (PCR-RFLP) method. Results A statistically significant difference in 2245A minor allele frequency was found between control (5.5) and DR groups (15.2) (p<0.001, OR=3.06, 95 CI 1.87 to 5.02) as well as between DNR (8.2) and DR (15.2) groups (p<0.01, OR=2.01, 95 CI 1.24 to 3.27). However, when the frequency was compared between control and DNR groups, there was no significant difference (p>0.05). Conclusions This is the first study that shows an association between the 2245A allele of the RAGE gene and development of diabetic retinopathy in the Malaysian population.